2017
DOI: 10.1080/14767058.2016.1271406
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based biomarkers of adverse perinatal outcomes in maternal obesity

Abstract: There is a critical need for reliable blood-based biomarkers associated with an increased risk of adverse perinatal outcomes in obese pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As stated by Herrera et al [48], a better understanding for biological processes linking maternal obesity with adverse perinatal outcomes is needed. At present time, no biomarkers are fulfilling the criteria to be used in clinic to predict perinatal complications [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by Herrera et al [48], a better understanding for biological processes linking maternal obesity with adverse perinatal outcomes is needed. At present time, no biomarkers are fulfilling the criteria to be used in clinic to predict perinatal complications [48].…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Herrera et al [48], a better understanding for biological processes linking maternal obesity with adverse perinatal outcomes is needed. At present time, no biomarkers are fulfilling the criteria to be used in clinic to predict perinatal complications [48]. Although previous studies support theories of inflammatory pathways, actions of specific inflammatory mediators, and inflammatory properties of the placenta, much is unknown and more research is needed [48].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found maternal prepregnancy overweight and obesity to be associated with overall stillbirth or neonatal death, and death due to specific causes such as placental dysfunction, umbilical cord complication, intrapartum events, and infection was more common in women with obesity. Although several biomarkers have been suggested to identify obese women at higher risk of pregnancy complications including stillbirth and neonatal death, none are considered clinically useful yet [ 63 , 64 ]. Ultrasound scans are today used for the screening of high-risk women, alone or in combination with biomarkers, but its specific application in stillbirth, especially in a broader population such as women with overweight or obesity, still needs to be proven in large clinical studies, which in itself is a great challenge due to the rarity of the outcome [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers could potentially be used as screening tools to identify population at risk, and to predict outcomes for the mother and offspring. However, the applicability of these biomarkers in a clinical setting is limited and requires more information, particularly among the obese population [30]. For example, it is generally known that low folate levels increase the risk of neural tube defects in offspring, while first trimester inflammatory cytokines are associated with increased risk of preterm birth among obese women [31][32][33].…”
Section: Introductionmentioning
confidence: 99%